Viabilidade técnica e ambiental da utilização de resíduos de madeira para a produção de um combustível alternativo - Artur Torres Filho (2005)
Wood wastes are often associated to problems in landfill disposal. In spite of the natural tendency of the use of these materials in combustion processes, the most part is being landfilled without use, due to several deadlocks such as uneven shape of the pieces, eventual presence of strange elements in the ligneous material (nails and wires), the excessive humidity, the low calorific power, among other facts that result in a great quantity of these materials being daily discharged. Trees pruning in large urban areas, waste from building construction as well as wooden waste deriving from industrial procedures are some of thematerial evaluated in this work in order to test the feasibility of their transformation into a solid fuel with adequate characteristics for use in thermal energy production, achieving economic value in the fuel market.Different treatments were applied involving mechanical procedure to obtain splinters of regular size, and their thermal processing at temperature range from 160º to 260º C for fifteen minutes, in laboratory and industrial scale, evaluating the increment in the calorific value. Theweight loss in industrial scale showed variation from 10.50% to 21.53% with an energetic yield varying between 87.51 and 96.88%. The comparison between the results obtained in laboratory and industrial scales varied within a range of 1.82% to 17.23%. The gross calorificvalue of the product obtained in several treatments, in industrial scale, varied between 4,653 and 4,796 kcal/kg. Application tests of the obtained product were undertaken in a bakery furnace, with isokinetic sampling of particles in the stack gases, in order to evaluate the level of particles emission in the atmosphere, comparing the emission with the results when using other biomass fuels. The rate of particle emission per kilogram of fuel burnt was 4.57 g/kg with the furnace using conventional timber; 2.77 g/kg with the furnace using the splinters without thermal treatment and 1.73 g/kg with the unit operating with the splinter thermallyprocessed.